Is the inclusive entrepreneurial intention among women ex-prisoners a perspective of reintegration in Tunisia? - Bardaa Mohamed Amin (African Scientific Journal, 2023)
Inclusive entrepreneurship refers to the participation of marginalized groups in entrepreneurship to help them overcome social and economic challenges, which plays a very important role in poverty reduction. This study proposes that the main solution to this problem is to promote inclusive entrepreneurship through the production of inclusive and innovative services and goods. Among unconventional and marginalized entrepreneurs: women ex-prisoners. Planned Behavior Theory is used to predict inclusive entrepreneurial intention which may be the key to filling existing gaps in understanding the intention of female ex-prisoners to be inclusive entrepreneurs by also testing the moderating effect of Planned Behavior Theory to compare women’s behavioral traits to inclusive entrepreneurial intention. The results of the regression analysis show that attitude, subjective norms and perceived behavioral control are significant in relation to inclusive entrepreneurial intention among female ex-prisoners. In conclusion, this study suggests that “inclusive entrepreneurship” may be a viable solution to the problem observed in society and to unconventional female entrepreneurs, as entrepreneurship could be a more attractive option. Entrepreneurship can be like a solution for reintegration into society for women ex-prisoners.